Astrocyte–Oligodendrocyte–Microglia Crosstalk in Astrocytopathies - de Waard, Dieuwke Maria; Bugiani, Marianna (Frontiers in Cellular Neuroscience, 2020)
Defective astrocyte function due to a genetic mutation can have major consequences for microglia and oligodendrocyte physiology, which in turn affects the white matter integrity of the brain. This review addresses the current knowledge on shared and unique pathophysiological mechanisms of astrocytopathies, including Vanishing White Matter, Alexander Disease, Megalencephalic Leukoencephalopathy with Subcortical Cysts, Aicardi-Goutières Syndrome and Oculodentodigital Dysplasia. The mechanisms of disease include protein accumulation, unbalanced secretion of extracellular matrix proteins, pro- and anti-inflammatory molecules, cytokines and chemokines by astrocytes, as well as an altered gap junctional network and a changed ionic and nutrient homeostasis. Interestingly, the extent to which astrogliosis and microgliosis are present in these astrocytopathies is highly variable. An improved understanding of astrocyte-microglia-oligodendrocyte crosstalk might ultimately lead to the identification of druggable targets for these, currently untreatable, severe conditions.